Abordaje de enfermería centrado en gestante con preeclampsia severa más neumonía - Aguay Yaguachi, Roberth Alexander; Chuquimarca Aponte, Mario Hernan (Machala : Universidad Técnica de Machala, 2022)
Introduction: Preeclampsia is a pathology that mainly affects the fetus due to an increase in blood pressure, which causes suffering for the future child. Women under 20 years of age, over 35 years of age and primiparous women are the ones with the highest risk, especially if they do not have proper control during pregnancy. We are talking about preeclampsia when blood pressure exceeds 140/90 mm Hg and proteinuria of more than 30 mg in a single sample or more than 300 mg in a 24-hour sample. It is caused by various factors, there is no apparent cause, but we know that having an unbalanced diet can cause this condition. On the other hand, pneumonia is defined as an inflammation of the lung parenchyma and alveolar spaces caused by infectious agents, the symptoms can vary such as difficulty breathing, coughing with or without expectoration, and sweating, it can be fatal for both the mother and the child. the product. The environmental factors that favor the infection of these microorganisms are an environment contaminated especially by excrement or fuel for cooking, in homes that are overcrowded and homes where there are smokers in addition to presenting said infection. The objective of this work is to establish the nursing approach focused on pregnant women with severe preeclampsia plus pneumonia based on Virginia Henderson's theory through scientific research for the improvement and control of pregnant women. The type of study was clinical since our object of study is a hospitalized patient, it is of an analytical type because it explains the relationship of cause and effect of preeclampsia and pneumonia in an orderly and systematic way, that is, from the general to the particular.
La preeclampsia es una patología que afecta principalmente al feto debido a una elevación en la tensión arterial lo que provoca un sufrimiento para el futuro producto. Mujeres menores de 20 años, mayores de 35 años y primigestas son las que mayor riesgo presentan, especialmente si no llevan un correcto control durante el embarazo. Hablamos de preeclampsia cuando la presión arterial supera los 140/90 mm Hg y proteinuria de más de 30 mg en muestra única o más de 300 mg en muestra de 24 horas. Esta patología es provocada por diversos factores y no existe una causa aparente, pero sabemos que teniendo una dieta desbalanceada puede provocar esta condición. Otra patología agregada es la neumonía que se define como una inflamación del parénquima pulmonar y de los espacios alveolares provocada por agentes infecciosos, los signos y síntomas pueden ser: disnea, tos con expectoración, fiebre mayor a 37,8 grados, escalofríos, cianosis, diaforesis y presencia de crepitantes pulmonares, estas características fisiopatológicas pueden resultar fatales para la gestante. El objetivo de este trabajo es establecer el abordaje de enfermería centrado en gestantes con preeclampsia severa más neumonía basada en la valoración por necesidades de la teoría de Virginia Henderson a través de la investigación científica para mejorar y controlar la salud materna. El tipo de estudio es clínico ya que nuestro caso fue una paciente hospitalizada, es de tipo analítico porque explica la relación de causa y efecto de la preeclampsia y neumonía en forma ordenada y sistematizada.
Keywords: PREECLAMPSIA; NEUMONIA; ABORDAJE DE ENFERMERIA